Registered nurses’ perceptions of their leadership close to older adults in municipal home healthcare: a cross-sectional questionnaire study - Erica Lillsjö; Anna Willman; Lise-Lotte Jonasson; Karin Josefsson (BMC Nursing)
Abstract Background Registered nurses lead the nursing care close to older adults in home healthcare. It is expected that there will be an increased need for home healthcare. In addition, more advanced care is now being performed in home healthcare, leading to increased demands for registered nurses. Therefore, the aims of this study are to explore and compare registered nurses’ perceptions of their leadership close to older adults in municipal home healthcare, as well as to correlate their perceptions with age and work experience. Methods This study is a part of a larger web-based questionnaire survey, with a non-experimental and cross-sectional design. Descriptive and analytical statistics were used. A total of n = 71 registered nurses leading close to older adults participated, in seven municipalities in two geographic areas in Sweden. Results The registered nurses perceived their ability as leaders close to older adults as high. The registered nurses had neither low or high trust in care staff’s competence. They perceived to have space and access neither in a low or high degree in their work to develop sufficient competence in leadership and having nursing responsibility on an organisational level. Registered nurses’ perceptions of their leadership differed depending on whether they had a specialist education or not; those with specialist education perceived to a higher degree that they could apply their professional experience in their work; interact with the older adult and their next of kin; assess individual needs and based on a holistic view of the older adult, create good relationships with the older adults’ next of kin. Conclusions Registered nurses’ specialist education may strengthen their leadership in home healthcare. Further research is needed to gain new knowledge of registered nurses’ leadership in home healthcare, as well as care staff’s’ experiences of registered nurses’ leadership in municipal home healthcare.